2021
DOI: 10.3390/pharmaceutics13081177
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Macroporous Silica—Nanocrystalline Cellulose Combination for Formulating Dry Emulsion Systems with Improved Flow Properties: A DoE Study

Abstract: The objective of this study was to explore the possible use of a new combination of two excipients, i.e., nanocrystalline cellulose (NCC) and macroporous silica (MS), as matrix materials for the compounding of dry emulsion systems and the effects these two excipients have on the characteristics of dry emulsion powders produced by the spray drying process. A previously developed liquid O/W nanoemulsion, comprised of simvastatin, 1-oleoyl-rac-glycerol, Miglyol 812 and Tween 20, was employed. In order to comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…The results obtained in this experiment theoretically confirm that the ratio of C/H in hydrocarbon species is strongly correlated with the sticking efficiency of the hydrogenated film reaction behaviors, and the sticking efficiency improves with the increasing of the C/H ratio [8,9]. Our experimental results further verify the theory that the C/H ratios obtained using C 2 H 2 are higher than those obtained using C 3 H 6 .…”
Section: Resultssupporting
confidence: 84%
“…The results obtained in this experiment theoretically confirm that the ratio of C/H in hydrocarbon species is strongly correlated with the sticking efficiency of the hydrogenated film reaction behaviors, and the sticking efficiency improves with the increasing of the C/H ratio [8,9]. Our experimental results further verify the theory that the C/H ratios obtained using C 2 H 2 are higher than those obtained using C 3 H 6 .…”
Section: Resultssupporting
confidence: 84%
“…Authors using spray-dried emulsions containing simvastatin or its analogues reported achieving a drug content of approximately 15 to 29 mg/g. However, their final drug delivery systems were mainly dry emulsions that were further processed into various solid dosage forms [ 51 , 52 , 53 ]. In our study, the theoretical drug content ranged from 41.7 mg/g to 76.9 mg/g depending on the antiadhesive used.…”
Section: Resultsmentioning
confidence: 99%
“…The moisture content of dry emulsions adsorbed with Avicel ® PH-101 (3.37 ± 0.07%) exceeded that of Aerosil ® 200 (2.00 ± 0.08%). Both dry emulsions demonstrated moisture contents within the general range (less than 3.5%) [90,91]. However, specific moisture content requirements may vary based on the formulation, type of adsorbent, and the drying process [35].…”
Section: Fabrication Of Dry Emulsionsmentioning
confidence: 99%